Using concurrent reinforcement schedules and prompts to produce varied manding: A replication of Seaver and Bourret (2020). (8th November 2022) - Seaver, Jonathan P.; Kelly, Michelle P.; Murray, Clodagh M.; Baruni, Rasha R.
Abstract: Deficits in social communication and restricted, repetitive patterns of behavior or interests are displayed by individuals with autism spectrum disorder (ASD; American Psychiatric Association, 2013). Given this, individuals with ASD may engage with a limited variety of reinforcers. Treatments designed to modify the distribution of manding may allow individuals to contact a broad array of reinforcers that could improve the quality of life for individuals with ASD (Seaver & Bourret, 2020). The purpose of the current study was to replicate the results of Seaver and Bourret (2020) by evaluating the effects of manipulating concurrent schedules of reinforcement, alone and with prompts, on the rates of target manding in three boys with ASD, aged 7–9 years, in the United Arab Emirates. All three participants showed increased target manding following intervention. The findings support the use of concurrent reinforcement schedules and prompts as an effective intervention to produce varied manding.